2010
DOI: 10.1371/journal.pgen.1001082
|View full text |Cite
|
Sign up to set email alerts
|

Methylated H3K4, a Transcription-Associated Histone Modification, Is Involved in the DNA Damage Response Pathway

Abstract: Eukaryotic genomes are associated with a number of proteins such as histones that constitute chromatin. Post-translational histone modifications are associated with regulatory aspects executed by chromatin and all transactions on genomic DNA are dependent on them. Thus, it will be relevant to understand how histone modifications affect genome functions. Here we show that the mono ubiquitylation of histone H2B and the tri-methylation of histone H3 on lysine 4 (H3K4me3), both known for their involvement in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
145
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 83 publications
(110 reference statements)
15
145
1
1
Order By: Relevance
“…In support of this, we find that An-swd1-deleted cells are sensitive to DNA damaging agents such as 1,2,7,8-Diepoxyoctane and MMS (data not shown). This is consistent with studies in S. cerevisiae and human cells that have shown that the Set1 complex functions in the DNA damage response (Corda et al 1999;Faucher and Wellinger 2010). Moreover, partial CDK1 activity in A. nidulans also results in sensitivity to DNA damaging agents (data not shown), potentially due to a reduced efficiency in recovering from DNA damage-mediated G2-M checkpoint arrest (Van Vugt et al 2005;Karlsson-Rosenthal and Millar 2006;Lindqvist et al 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In support of this, we find that An-swd1-deleted cells are sensitive to DNA damaging agents such as 1,2,7,8-Diepoxyoctane and MMS (data not shown). This is consistent with studies in S. cerevisiae and human cells that have shown that the Set1 complex functions in the DNA damage response (Corda et al 1999;Faucher and Wellinger 2010). Moreover, partial CDK1 activity in A. nidulans also results in sensitivity to DNA damaging agents (data not shown), potentially due to a reduced efficiency in recovering from DNA damage-mediated G2-M checkpoint arrest (Van Vugt et al 2005;Karlsson-Rosenthal and Millar 2006;Lindqvist et al 2009).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, H3K4 methylation is also involved in maintaining the repression of telomere proximal genes in S. cerevisiae and Schizosaccharomyces pombe and the suppression of secondary metabolite production in A. nidulans and A. fumigatus (Krogan et al 2002;Kanoh et al 2003;Bok et al 2009;Palmer et al 2013). Growing evidence indicates that the Set1 complex is involved in a gamut of additional cellular functions, many of which may be independent of its roles in gene expression, including kinetochore maintenance, DNA repair, and replication checkpoints (Faucher and Wellinger 2010;Bergmann et al 2011). Importantly the Set1 complex regulates mitosis in budding yeast with the Aurora mitotic kinase Ipl1 and the type1 phosphatase Glc7 (Zhang et al 2005;Latham et al 2011).…”
mentioning
confidence: 99%
“…H3K4 is methylated by Set1 in yeast cells (35), and Set1 has been suggested to be involved in DNA damage response because deletion of SET1 alleviated the DNA damage sensitivity of checkpoint-defective MEC3 deletion strain by derepressing the expression of DNA repair genes (36,37). In contrast, a more recent study showed that either SET1 deletion or H3K4A mutation enhances the DNA damage sensitivity of DNA repair-defective RAD50 deletion mutant cells (38). To determine whether methylation on H3K4 is involved in HU sensitivity, we knocked out SET1 in the H2A N-tail delete mutant strains (tH2A and tH2A:tH3K4A).…”
Section: Double Deletion Of the Histone N-tails Uncovers Unidentifiedmentioning
confidence: 99%
“…These results indicate that the activation of the HUmediated replication checkpoint but not of the DNA damage checkpoint is defective in tH2A:H3K4A cells. A single point mutation on H3K4 fails to bring about a prominent HU sensitivity (10,38). However, when H3K4A mutation or SET1 deletion was introduced into cells lacking RAD50, a DNA double-strand break repair factor, a more enhanced HU sensitivity was observed (38).…”
Section: Double Deletion Of the Histone N-tails Uncovers Unidentifiedmentioning
confidence: 99%
“…In the case of H3-K56 of yeast, acetylation is required to complete replication in the presence of lesions caused by methylmethane sulfonate (MMS) (Wurtele et al, 2012), and yeast cells defective in both CLR4 and SET2 (methyltransferases for H3-K9 and H3-K36, respectively) showed decreased RAD3 (fission yeast homolog of ATR)-dependent phosphorylation of CDC2 and MIK1 following hydroxyurea treatment, suggesting that hydroxyureainduced replication stress checkpoints require H3 methylation by CLR4 and SET2 (Kim et al, 2008). Furthermore, H3-K4 trimethylation may also contribute to repair of Sphase damage in S. cerevisiae, as the absence of SET1, a HMT responsible for H3-K4 trimethylation, leads to an Sphase progression defect (Faucher and Wellinger, 2010). Thus, histone modifications such as phosphorylation, acetylation and methylation may play a role in fork stall-related damage responses.…”
Section: Introductionmentioning
confidence: 99%